2000
DOI: 10.1007/s004390000320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CAG repeats in SCA1, SCA2, SCA3, SCA6, SCA7 and DRPLA loci in spinocerebellar ataxia patients and distribution of CAG repeats at the SCA1, SCA2 and SCA6 loci in nine ethnic populations of eastern India

Abstract: To identify various subtypes of spinocerebellar ataxias (SCAs) among 57 unrelated individuals clinically diagnosed as ataxia patients we analysed the SCA1, SCA2, SCA3, SCA6, SCA7 and DRPLA loci for expansion of CAG repeats. We detected CAG repeat expansion in 6 patients (10.5%) at the SCA1 locus. Ten of the 57 patients (17.5%) had CAG repeat expansion at the SCA2 locus, while four had CAG expansion at the SCA3/MJD locus (7%). At the SCA6 locus there was a single patient (1.8%) with 21 CAG repeats. We have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…The authors also found evidence of a common founding mutation 43 . Basu et al, investigating a series of nine different ethnic populations in India, concluded that SCA 2 was the most common 44 . Velazquez-Perez studied 125 families with SCA in Cuba and concluded that SCA 2 (present in 120 families) was the most common form.…”
Section: Scamentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also found evidence of a common founding mutation 43 . Basu et al, investigating a series of nine different ethnic populations in India, concluded that SCA 2 was the most common 44 . Velazquez-Perez studied 125 families with SCA in Cuba and concluded that SCA 2 (present in 120 families) was the most common form.…”
Section: Scamentioning
confidence: 99%
“…SCA 2 locus has been mapped to chromosome 12 (12q24.13), and the genetic mutation responsible for the disease is a CAG trinucleotide expansion with between 34 and 59 repeats [3][4][5][6][7][8][9][10][43][44][45] .…”
Section: Scamentioning
confidence: 99%
“…There is a wide variation in the prevalence of SCA1 amongst ADCA families between the different ethnic and geographical groups. It varies from as high as 41% in the South African and Russian ADCA pedigrees to intermediate in the Indian (7-16%), Italian (21%), German (9%), Chinese (7%) and Korean (12%) ADCA families and has an extremely low prevalence in Taiwan (1.2%) (Illarioshkin et al 1996;Schols et al 1997;Basu et al 2000;Saleem et al 2000;Zhou et al 2001;Bryer et al 2003;Lee et al 2003;Brusco et al 2004;Sinha et al 2004;Tsai et al 2004). Even within the Japanese population, the prevalence is very heterogeneous varying from 3% to 25% (Takano et al 1998;Onodera et al 2000;Sasaki et al 2000;Maruyama et al 2002;Matsumura et al 2003;Sasaki et al 2003).…”
Section: Introductionmentioning
confidence: 96%
“…The disease is progressive and patients become dependent on others within a few years of onset. SCA-2 is among the three (with SCA3 and SCA6) most frequent types of SCAs worldwide [1,7,8,] whereas it has been reported as the most common SCA phenotype in India [9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%